Characterization of potential elastase inhibitor-peptides regulated by a molecular switch for wound dressings applications - Barros, Sandra Cerqueira (2012)
Elastase plays an important role in wound healing process, degrading damaged tissue and allowing complete tissue recovery. The levels of human neutrophil elastase (HNE) are usually controlled by endogenous inhibitors. However, in the presence of high levels of elastase, like the ones present in chronic wounds, the inhibitors cannot overcome this overproduction and the enzyme starts to degrade the surrounding healthy tissue. In this work we report the development of a molecular switch to control the elastase activity in the exudate of non-healing chronic wounds. A peptide library was generated and screened in a microarray format for protein kinase-mediated phosphorylation. Two peptides were identified as casein kinase Iδ (CKI) substrates: KRCCPDTCGIKCL and its analogous peptide KRMMPDTMGIKML, with cysteine residues replaced by methionine residues. These peptides were studied in solution, both in the phosphorylated and non-phosphorylated forms as potential inhibitors for elastase. The obtained results show that the reversible process of phosphorylation/dephosphorylation results in differential inhibitory activity of the peptides. Thus the reversible process of phosphorylation/dephosphorylation can be used as a kind of molecular switch to control elastase activity. Degradation studies reveal that both the inhibitor-peptides and CKI are degraded by elastase. These results envisage the safe utilisation of these inhibitor-peptides together with CKI in the formulation of wound dressings.